2004
DOI: 10.3748/wjg.v10.i17.2493
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori cagA,iceAandvacAgenotypes in patients with gastric cancer in Taiwan

Abstract: In Taiwan, H pylori with positive vacA s1a, cagA and iceA1 strains are found in the majority of patients with gastric cancer or non-cancer patients. In patients with gastric cancer, the vacA s1a and s1c subtypes are less and m1T is more than in patients with peptic ulcer and chronic gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 47 publications
3
10
1
Order By: Relevance
“…The s1b types are rare in other regions and less virulent than other s1 subtypes (2,3,10,19,20,22,23). Furthermore, although the s1c allele has been stated to be more common in Asian strains and it may be associated with gastric cancers that are prevalent in that region, other studies have, in contrast, indicated that cancer development cannot be explained by s1c alleles alone (4,12,(18)(19)(20)23). Thus, the relationship between the genotypes of causative strains and clinical outcome should be considered in different geographic regions in order to make a true estimation of prognosis.…”
mentioning
confidence: 70%
“…The s1b types are rare in other regions and less virulent than other s1 subtypes (2,3,10,19,20,22,23). Furthermore, although the s1c allele has been stated to be more common in Asian strains and it may be associated with gastric cancers that are prevalent in that region, other studies have, in contrast, indicated that cancer development cannot be explained by s1c alleles alone (4,12,(18)(19)(20)23). Thus, the relationship between the genotypes of causative strains and clinical outcome should be considered in different geographic regions in order to make a true estimation of prognosis.…”
mentioning
confidence: 70%
“…In both studied groups, we found H. pylori strains that were untypeable for the signal-sequence and mid-region alleles due to significant variation in the vacA gene [8], [24]. We consistently found that the cagA - and vacA -allele diversity was greater in the tumor, suggesting that H. pylori can remain in the tumor without environmental stress.…”
Section: Discussionmentioning
confidence: 95%
“…pylori strains. However, most of the vacA s regions were of the s1a subtype, which is less frequently found in patients with gastric cancer than in those with peptic ulcers and chronic gastritis [ 47 ] or is present only in dyspeptic patients [ 48 ]. In addition, the predominant m region subtype was m1c, which is specific to South Asian countries with a low ASR of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%